AB0411 Comparison of tuberculin skin test and interferon-gamma release assay screening in patients with rheumatoid arthritis starting anti-tumor necrosis factor therapy. (15th June 2017) - Archimandriti, DT; Iliou, C; Tzallas, AT; Pelechas, E; Drosos, AA; Voulgari, PV
Abstract : Background: Biologic agents provide clinical benefits in patients with Rheumatoid Arthritis (RA) but they are associated with an increased risk of tuberculosis (TB) infection. Objectives: We investigated the accordance between the tuberculin skin test (TST) and the interferon-gamma (IFN-γ) release assay (IGRA) for the diagnosis of latent tuberculosis infection (LTBI) in patients with RA. The objective of our study was a direct comparison between the IGRA and the TST regarding LTBI diagnosis in RA patients before starting anti-TNF agents and at least one year after the initiation of treatment. Methods: RA consecutive patients have been included in the study both before and after 1 year of the initiation of TNF-α antagonist therapy. A standard questionnaire was completed for each patient, including basic demographic data and concurrent immunosuppressive therapy (corticosteroids, disease-modifying anti-rheumatic drugs [DMARDs], synthetic and biologics). The patients were screened for LTBI using IGRA and TST methods. All analyses were performed with IBM-SPSS Statistics for Windows (version 21). The kappa coefficient (κ) was calculated to determine the concordance between the two tests: TST and IGRA. The strength of the agreement was considered "poor" for κ ≤0.20, "low-moderate" for 0.20 < κ ≤0.40, moderate for 0.40 < κ ≤0.60, "substantial" for 0.60 < κ ≤0.80, and "optimal" for 0.80 < κ ≤1. Results: 78 patients (67 female, 11 male) have been screened with TST and IGRA. The accordance between TST and IGRA was 89.7% (κ 0.514, κ<0.001). A κ value of 0.514 represents a moderate accordance between the two tests. 6 female patients converted TST (4 became positive, and 2 became negative). No patient developed active tuberculosis. Conclusions: A moderate accordance between the two methods (TST and IGRA) was obtained. In the absence of a diagnostic gold standard for LTBI, different issues should be taken into consideration regarding the two methods (cost, laboratory expertise and equipment etc). More studies are needed in the field in order to elucidate the cost-effectiveness but also the appropriateness of both methods. Disclosure of Interest: None declared